2020
DOI: 10.3390/medicines7090057
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Content and In Vitro Biological Activities of Commercial Cannabidiol Oils and Hemp Seed Oils

Abstract: Background: Hemp (Cannabis sativa L.) seed contains high contents of various nutrients, including fatty acids and proteins. Cannabidiol (CBD) is a non-psychoactive compound that can be extracted from C. sativa and used for treating epilepsy and pain. Industrial hemp products, including CBD and hemp seed oils, have become increasingly popular. Some products are marketed without a clear distinction between CBD and hemp seed oils. Herein, the CBD content and biological activities of commercial CBD and hemp seed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Our results are partially consistent with findings observed by Kitamura et al 48 , who performed ABTS and DPPH assays on CBD oil samples and obtained EC50 values ranging from 67 to 138 µM in the ABTS assay and from 522 to 1075 µM in the DPPH assay, concentrations reaching the same order of magnitude as that reported for the concentrations obtained in the present study. Interestingly, in line with the results of Floegel and colleagues 49 , the antioxidant capacity detected by ABTS assay was significantly higher for phytoderivatives than that detected by DPPH assay, as reported in Fig.…”
Section: Resultssupporting
confidence: 93%
“…Our results are partially consistent with findings observed by Kitamura et al 48 , who performed ABTS and DPPH assays on CBD oil samples and obtained EC50 values ranging from 67 to 138 µM in the ABTS assay and from 522 to 1075 µM in the DPPH assay, concentrations reaching the same order of magnitude as that reported for the concentrations obtained in the present study. Interestingly, in line with the results of Floegel and colleagues 49 , the antioxidant capacity detected by ABTS assay was significantly higher for phytoderivatives than that detected by DPPH assay, as reported in Fig.…”
Section: Resultssupporting
confidence: 93%
“…Cannabinoids protect against oxidative stress in the cell [ 13 ], and cannabinoid-like CBD has anxiolytic, antipsychotic, and antidepressant properties [ 24 ]. However, in fresh Cannabis sativa L. plants, CBD exists primarily in the carboxylated form, cannabidiolic acid [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower antioxidant property of CBD-W could be due to the presence of surfactants in the reaction mixture where CBD is solubilized in a micelle and less accessible to DPPH molecules. Kitamura et al 45 performed DPPH assays on CBD oil samples and obtained EC 50 values 522 to 1075 μM (164 to 338 μg mL −1 ). Russo et al 46 also observed EC 50 values around 3180 μM (1000 μg mL −1 ), much higher than the values obtained in this study.…”
Section: Resultsmentioning
confidence: 99%